Synthesis, characterisation and biological activities of mixed ligand oxovanadium (IV) complexes derived from N,N-diethyl-N′-para-substituted-benzoylthiourea and hydrotris(3,5-dimethylpyrazolyl)borate - Al-abbasi, Aisha A.; Mohamed Tahir, Mohamed Ibrahim; Kayed, Safa Faris; Kassim, Mohammad (Wiley, 2022)
A series of oxovanadium (IV) complexes namely, [Tp*VOL1], [Tp*VOL2], [Tp*VOL3], [Tp*VOL4] and [Tp*VOL5] (where Tp = hydrotris(3,5-dimethylpyrazolyl)borate, HL1 = 1-benzoyl-3,3-diethylthiourea, HL2 = 1-(4-chlorobenzoyl)-3,3-diethylthiourea, HL3 = 1,1-diethyl-3-(4-methoxybenzoyl)thiourea, HL4 = 1,1-diethyl-3-(4-nitrobenzoyl)thiourea, HL5 = N-(diethylcarbamothioyl)biphenyl-4-carboxamide) were prepared and characterised on the basis of mass spectrometry, elemental analysis and spectroscopy techniques (IR, UV–Vis and electron paramagnetic resonance, EPR) and mass spectrometry. The crystal structure of [Tp*VOL3] was elucidated from single crystal X-ray diffraction study and the crystals adopted a triclinic system with a P-1 (Z = 2) space group and unit cell parameters of a = 10.4953(4), b = 11.5290(5) and c = 15.0656(7) Å. The cyclic voltammetry showed a reversible oxidation of V (IV)/V(V) at about 0.50 V (vs Fc+/Fc). The HOMO and LUMO of benzoylthiourea were established by theoretical calculation based on DFT level using B3LYP method and a double numeric plus polarisation (DNP) basis set. The in vitro tests for antimicrobial activity showed that the complexes have a moderate inhibitory effect. The complex [Tp*VOL1] exhibited cytotoxic activity against the human hepatocellular carcinoma cell line (HepG2) at the concentration of 20 mg ml−1. However, no cytotoxic activity was observed against the Chang liver cells.